PENERAPAN SANKSI EDUKATIF DALAM PENINGKATAN KEDISIPLINAN PESERTA DIDIK DI MTS SEMESTA KEDUNGMALING SOOKO MOJOKERTO - Moch. Sya’roni Hasan; Hanifa Rusydiana (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2018)
This study discusses the Application of Educational Sanctions in Increasing Discipline of Students in MTs Semesta Kedungmaling Sooko Mojokerto. The approach in this study is a qualitative type case study. In collecting data used participant observation methods, in-depth interviews and documentation. The data analysis technique uses an interactive analysis model that includes several interrelated components, namely data collection, data reduction, data presentation and conclusion drawing. To check the validity of the data used extension of research, persistence of observation, and triangulation. The results of research on educational sanctions are (1) Socialization. At this stage the madrasa invites parents of students to sign a Memorandum of Understanding regarding the application of the rules and sanctions given. (2) Trial. Implementation of educational sanctions also needs to be tested, namely for 1 month with a duration of time from 12.00 to 13.00 WIB. (3) Implementation. First: Executor I, in KBM (Teaching and Learning Activities). Educators in the class have the right to reprimand, warn and record even the right to sanction students who have problems before being followed up by executor II. Second: Executor II (educator in charge of discipline) analyzes and interrogates student mistakes. After finding out the mistake, while being given a punishment, students are also given soft therapy and motivation not to repeat their mistakes again.